2004
DOI: 10.1021/la048177k
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of μ-Contact Printed Protein Patterns by SPR Imaging with a LED Light Source

Abstract: We demonstrate the characterization of mu-contact printed protein patterns and analysis of protein-protein interactions by two-dimensional (2-D) surface plasmon resonance imaging (SPRi). Advancements in SPRi image quality from employing a light emitting diode (LED) as the light source are described. We show that a LED offers an ideal point source that can eliminate interference artifacts and speckles found when using a laser source. The attainable thickness resolution in fixed-angle imaging is comparable to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 44 publications
1
77
0
Order By: Relevance
“…[183] SPR has been further developed in an imaging technique that is sensitive and label free for visualizing the whole of the biochip via a video charge-coupled device camera. [204][205][206] The biochips can be prepared in an array format with each active site providing SPR information simultaneously. It captures all of the local changes at the surface of the biochip providing detailed information on molecular binding, biomolecular interactions, and kinetic processes.…”
Section: Mechanistic View Of Spr In Metal Nanoparticlesmentioning
confidence: 99%
“…[183] SPR has been further developed in an imaging technique that is sensitive and label free for visualizing the whole of the biochip via a video charge-coupled device camera. [204][205][206] The biochips can be prepared in an array format with each active site providing SPR information simultaneously. It captures all of the local changes at the surface of the biochip providing detailed information on molecular binding, biomolecular interactions, and kinetic processes.…”
Section: Mechanistic View Of Spr In Metal Nanoparticlesmentioning
confidence: 99%
“…SPR imaging applications typically fall into the areas of genomics and proteomics. Some examples of genomics applications include DNA-DNA (Wark et al, 2005;He et al, 2000), DNA-RNA (Nelson et al, 2001), and DNA-drug (Wolf et al, 2005) interactions. For proteomics, the applications include determining protein thickness (Otsuki et al, 2005;Wilkop et al, 2004), conformational changes , and expression profiling (Usui-Aoki et al, 2005).…”
Section: Surface Plasmon Resonance Imagingmentioning
confidence: 99%
“…Some examples of genomics applications include DNA-DNA (Wark et al, 2005;He et al, 2000), DNA-RNA (Nelson et al, 2001), and DNA-drug (Wolf et al, 2005) interactions. For proteomics, the applications include determining protein thickness (Otsuki et al, 2005;Wilkop et al, 2004), conformational changes , and expression profiling (Usui-Aoki et al, 2005). Other diverse application areas for SPR imaging include toxin-binding inhibition in glycomics (Kanda et al, 2005), self-assembled monolayers (Pyo et al, 2005), detection of human choriogonadotropin (Piliarik et al, 2005), and fabrication of electrochemical switches (Arena et al, 2004).…”
Section: Surface Plasmon Resonance Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…SPR-based technology is an accepted and established tool for investigation of biological processes, adsorption phenomena, characterization of binding properties of antibodies and other biological molecules, gene analysis and drug discovery [17][18][19][20][21][22][23][24]. Recently, we have shown that a high resolution SPR can be used to detect and quantify heavy metal ions in drinking water [25].…”
Section: Introductionmentioning
confidence: 99%